Three periods, Three Cultures and Three Charactrs of Tawaef : (Khanam Jan, Umrao Jan Ada, Laila) - Dr Khawer Nawazish; Muhammad Khawar Ali (Zaban-o-Adab, 2021)
The study of the social, psychological and cultural status of a woman is now a subjective matter but initially it was considered by some feminist ideologues. Literary writings especially fiction is very important for feminist, social, anthropological and gender studies. In Urdu fiction, women have been portrayed in different perspectives, one of which is a prostitute. This research article represents a comparative study in social and cultural background of miscellaneous characters of prostitutes presented in three famous Urdu novels; ’Nishtar’, ’Umrao Jan Ada’ and ’Laila Kay Khatoot’. These novels are not simply the stories of three prostitutes but also give us the glimpse of the political and cultural environment of the time with which these three characters are related. This study shows that the strongest character of prostitute among three is that of "Amrao Jan" while the strongest reaction against masculine society and for forcefully pushing an ordinary girl into the profession of prostitute comes from "Laila". Third character "Khanum Jan"; despite being a prostitute, falls in true love with a man and never been into any physical relationship with anyone. Moreover, it has also been observed that Munshi Sajjad Hussain in ’Nishtar’, Mirza Hadi Riswa in ’Umrao jan Ada’ and Qazi Abdul Ghafar in ’Laila Kay Khatoot’ have tried to write a parallel cultural history of three different areas of Hidustan i.e Kanpur, Lacknow, Aligarh and Haiderabad.